The The Influence of Motivation, Communication and Work Environment on Remote Work Satisfaction in PT Employees. Smartfren Yogyakarta - Ubaidillah, Ahmad Sulthon (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
The purpose of this study was to determine the effect of Motivation, communication and work environment on Remote Work Satisfaction at PT Smartfren Yogyakarta which has motivation problems from fellow coworkers resulting in a lack of enthusiasm in employees, besides the lack of good communication between fellow employees resulting in a lack of support between employees with each other. The sample used in this study was 82 employees. the method used to collect data by distributing questionnaires is done through distributing questions arranged in a collection to respondents. The method used to collect data by means of observing or reviewing carefully and directly at the research location to find out the conditions that occur.Based on the results of the research conducted, the following conclusions can be drawn: There is a significant positive influence between motivation and work environment on Remote Work Satisfaction in employees of PT Smartfren Yogyakarta and there is a communication that is not significant positive on Remote Work Satisfaction in employees of PT Smartfren Yogyakarta. Keywords: Motivation; Communication; Work environment; Remote work satisfaction